2021
DOI: 10.1115/1.4049374
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Coupled Train-Bridge-Bearing System Under Earthquake- and Train-Induced Excitations

Abstract: The dynamic interaction between a bridge and a moving train has been widely studied. However, there is a significant gap in our understanding of how the presence of isolation bearings influences the dynamic response, especially when an earthquake occurs. Here, we formulate a coupled model of a train-bridge-bearing system to examine the bearings’ dynamic effects on the system responses. In the analysis, the train is modeled as a moving oscillator, the bridge is a one span simply supported beam and one isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Our previous work [ 46 ] proposed a strategy to build an efficient state‐space model of a simply supported beam based on the modal decomposition method. In the following sections, this strategy is adopted and extended to establish the SSEs for the three motions of the bridge section.…”
Section: Model Of the Train–wheel–bridge–bearing Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work [ 46 ] proposed a strategy to build an efficient state‐space model of a simply supported beam based on the modal decomposition method. In the following sections, this strategy is adopted and extended to establish the SSEs for the three motions of the bridge section.…”
Section: Model Of the Train–wheel–bridge–bearing Systemmentioning
confidence: 99%
“…It has been demonstrated that using the first five modes (N=5$N=5$) in the simulation would achieve sufficient accuracy. [ 46 ] Since the bridge's horizontal and vertical modal shape functions are identical, both are represented by ϕı,n(xı)$\phi _{\imath ,n}(x_\imath )$.…”
Section: Model Of the Train–wheel–bridge–bearing Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to eliminate the visual interference caused by different orders of magnitude such as Figure 5A,B, the error is further explained by Figure 6. Different from NRMSD, the Error(t) is used to judge the error value between the contact force calculated by the simplified model and by the Hertz model at each time t, which is determined by Equation (20).…”
Section: Vertical Contact Forcementioning
confidence: 99%